ANALYSIS OF HOLT-WINTERS AND ARIMA MODEL IN MUSLIMAH SCARF DEMAND FORECASTING - Vita Sarasi; Iman Chaerudin; Nugroho Djati Satmoko; Destiana Ayuningtyas Zahra (Fakultas Ekonomi dan Bisnis Universitas Padjadjaran, 2023)
Scarf and Muslimah clothing are popular phenomenon that can become a trend in Indonesia as an expression of cultural identity and communication. Demand forecasting in the fashion industry is one of the most important elements in an operational decision support system that significantly influences inventory management. Rapid changes in fashion cause the number of demand to be uncertain and cause forecasting discrepancies, which can lead to overstock. The purpose of this research is to design a forecasting method using the Holt Winters Model for four products and the ARIMA Model (0,1,1) for one product. The result is that by using these two forecasting models, the amount of overstock decreased by 5.6% and cost savings of IDR 67,742,481.04 for nine months. The proposed amount of safety stock is at the service level of 90 to 95%